The rising incidence of heterotopic pregnancy: Current perspectives and associations with in-vitro fertilization. (November 2021) - Maleki, Aryan; Khalid, Noorulain; Rajesh Patel, Chandni; El-Mahdi, Essam
Abstract: Heterotopic pregnancy is the simultaneous occurrence of an intrauterine and ectopic pregnancy. This study aims to review the current literature regarding heterotopic pregnancy with a focus on its diagnosis and associations with in-vitro fertilization (IVF). Studies have shown that ovarian hyperstimulation syndrome and multiple embryo transfer during IVF are associated with an increased risk of heterotopic pregnancy. Tubal abnormalities such as pelvic inflammatory disease and previous tubal or abdomino-pelvic surgery have also been identified as risk factors. Diagnosis is challenging as the falsely reassuring presence of an intrauterine fetus frequently delays early intervention. Treatment should be individualised, but is often prompt surgical intervention, and focuses on terminating the ectopic pregnancy while minimizing harm to the mother and intrauterine fetus.